Factors Associated With The Incidence Of Anaemia In Grade X Students At Sman 1 Sukahaji, Majalengka District In 2023 - Kumalasary, Diyanah; Triwahyuningsih, Ria Yulianti; Muliawaty, Lia; Hidayah , Fika Nurul; Rahmatika , Siti Difta; Faridah (International Journal of Midwifery and Health Sciences, 2024)
Anemia is a condition in which the number and size of red blood cells or hemoglobin levels fall below the set normal limit, resulting in disruption of the capacity of the blood to transport oxygen throughout the body. The incidence of anemia in Indonesia is 48.9% with the proportion of anemia in the age group 15-24 years namely 32%. The purpose of this study was to determine the factors associated with the incidence of anemia in class X students at SMAN 1 Sukahaji, Majalengka Regency in 2023. This type of research uses an observational analytic study with a cross sectional approach. The number of samples is 129 female students taken by probability random sampling from 187 female students. The data were analyzed using the Chi-Square statistical test. From the results of statistical tests, it was found that there was a relationship between nutritional status (p=0.017), menstrual cycle (p=0.014), menarche (p=0.000), knowledge about anemia (p=0.000) and adherence to taking iron supplement tablets (p=0.000 ) with the incidence of anemia in class X students at SMAN 1 Sukahaji, Majalengka Regency in 2023. It was concluded that nutritional status, menstrual cycle, menarche, knowledge about anemia and adherence to taking blood supplement tablets are factors associated with anemia in class X students at SMAN 1 Sukahaji, Majalengka Regency in 2023. It is recommended for female students to increase consumption of iron and protein and it is hoped that the role of parents or teachers to monitor female students in consuming iron tablets.